2019
DOI: 10.3847/1538-4357/ab38c4
|View full text |Cite
|
Sign up to set email alerts
|

The Shallow Decay Segment of GRB X-Ray Afterglow Revisited

Abstract: Based on the early-year observations from Neil Gehrels Swift Observatory, Liang et al. (2007) performed a systematic analysis for the shallow decay component of gamma-ray bursts (GRBs) X-ray afterglow, in order to explore its physical origin. Here we revisit the analysis with an updated sample (with Swift/XRT GRBs between February 2004 and July 2017). We find that with a larger sample, 1) the distributions of the characteristic properties of the shallow decay phase (e.g. t b , S X , Γ X,1 , and α X,1 ) still a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 79 publications
2
28
1
Order By: Relevance
“…Even if X-ray light curve has a break at t b , eight events (GRB 100728A, 110731A, 130427A, 130907A, 140102A, 150314A, 160325A and a VHE event GRB 180720B) have the pre-break decay index α1 larger than 0.7. For the sample of Zhao et al (2019), the distribution of the pre-break decay index has a mean of 0.43 and a dispersion of 0.22 (see dotted line in Fig. 2), hence the 8 events with α1 > 0.7 deviate from the mean value for ordinary GRBs more than 1σ.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Even if X-ray light curve has a break at t b , eight events (GRB 100728A, 110731A, 130427A, 130907A, 140102A, 150314A, 160325A and a VHE event GRB 180720B) have the pre-break decay index α1 larger than 0.7. For the sample of Zhao et al (2019), the distribution of the pre-break decay index has a mean of 0.43 and a dispersion of 0.22 (see dotted line in Fig. 2), hence the 8 events with α1 > 0.7 deviate from the mean value for ordinary GRBs more than 1σ.…”
Section: Discussionmentioning
confidence: 96%
“…with α1 and α2 describing the decay slopes of pre- and post-break segments, respectively, and t b is a break time. A smoothness parameter w is fixed to be 3 (Liang, Zhang & Zhang 2007;Zhao et al 2019). We compare above two models in order to determine whether the additional degrees of freedom in the DPL model are warranted over a simpler SPL model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The afterglow of GRBs is likely due to the external forward shock (ES) where the relativistic ejecta impacts the external medium (Paczynski & Rhoads 1993;Katz & Piran 1997;Meszaros & Rees 1997). It has already been shown that Swift GRB lightcurves (LCs) have more complex features than a simple power law (PL; Tagliaferri et al 2005;Nousek et al 2006;O'Brien et al 2006;Zhang et al 2006a;Sakamoto et al 2007;Zhao et al 2019). O'Brien et al (2006) and Sakamoto et al (2007) discovered the existence of a flat part in the X-ray LCs of GRBs, called the "plateau," which is present soon after the decaying phase of the prompt emission.…”
Section: Introductionmentioning
confidence: 99%